Balancing Caution and Expansion: The Non-Performing Loans Threshold for the Credit-Growth Nexus - Zuhroh, Idah; Rofik, Mochamad (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: This research explores how non-performing loans (NPLs) affect economic growth while assuming that the economy can sustain a certain ratio of NPLs without disruption. Background Problems: Studies employing the threshold approach have not explicitly defined the upper limit of NPLs that supports economic growth. Novelty: This study adds to the existing literature by examining the non-linear relationship between NPLs and economic growth, grounded in two key assumptions: 1) the complete elimination of NPLs is unrealistic, and 2) a threshold level of NPLs exists. Research Methods: Based on this assumption, the study constructs a non-linear model with an inverted U-shape pattern, applying annual data from 33 provinces in Indonesia during 2010–2021 and employing dynamic panel data regression with the GMM estimator. Finding/Results: The results reveal that NPLs will have a negative impact on growth when the NPL ratio exceeds 5.8% in total credit and 2.4% for household credit. However, no inverted U-shaped pattern is observed for working capital and investment credit. In addition, bank credit in total, as well as working capital credit and household credit show a significant positive coefficient on growth, while investment credit has an insignificant negative coefficient. We also introduce the concept of NPLs-growth risk, categorizing it as risk-free, low-risk, moderate-risk, and high-risk based on the area under the curve. The findings indicate that the NPLs-growth risk in Indonesia is generally at a low level. Conclusion: Ensuring that NPLs remain within a safe threshold is essential for sustaining economic growth and avoiding financial instability.